Nightflyers - Martin, George R. R. (New York : Bantam, 2018)
"Aliens meets Psycho with a chilling mystery set on a haunted spaceship in this illustrated edition of a classic novella, soon to be an original series on SYFY, by the #1 bestselling author of A Game of Thrones. When a scientific expedition is launched to study a mysterious alien race, the only ship available is the Nightflyer, a fully autonomous vessel manned by a single human. But Captain Royd Eris remains locked away, interacting with his passengers only as a disembodied voice--or a projected hologram no more substantial than a ghost. Yet that's not the only reason the ship seems haunted. The team's telepath, Thale Lasamer, senses another presence aboard the Nightflyer--something dangerous, volatile, and alien. Captain Eris claims to know nothing about the elusive intruder, and when someone, or something, begins killing off the expedition's members, he's unable--or unwilling--to stem the bloody tide. Only Melantha Jhirl, a genetically enhanced outcast with greater strength, stamina, and intelligence than other humans, has a chance of solving the mystery--and stopping the malevolent being that's wiping out her shipmates. But first she has to keep herself alive"--
"Aliens meets Psycho with a chilling mystery set on a haunted spaceship in this illustrated edition of a classic novella, soon to be an original series on SYFY, by the #1 bestselling author of A Game of Thrones. When a scientific expedition is launched to study an alien race, the only ship available is the Nightflyer--a mysterious ship whose equally mysterious captain remains locked away, refusing to interact with his new passengers in person. Worse, the mission's telepath, Melantha Jhirl, senses a presence aboard the ship: dangerous, volatile, and alien. And then, one by one, the passengers start dying. Only Melantha--genetically enhanced and able to think three steps ahead of most of humanity--has a chance of figuring out the mystery...if she can stay alive long enough"--
Keywords: Space ships -- Fiction; Murder -- Fiction; FICTION / Horror; Science fiction; Horror fiction